1994
DOI: 10.1001/archsurg.1994.01420350051005
|View full text |Cite
|
Sign up to set email alerts
|

Radiodetoxified Endotoxin—Induced Tolerance Alters Monocyte but Not Neutrophil CD11b and CD18 Expression in Response to Lipopolysaccharide

Abstract: Radiodetoxified endotoxin reduces mortality rates from bacterial peritonitis when given at least 72 hours prior to a bacterial inoculum. Tolerance to subsequent LPS challenge is associated with an abrogation of the reduced peripheral monocyte CD11b and CD18 expression observed in native LPS-stimulated mice but is not associated with changes in polymorphonuclear leukocyte CD11b and CD18 expression. The mechanism of the observed RDE-induced monocyte hyporesponsiveness to LPS and its possible protective effect is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 33 publications
2
4
0
Order By: Relevance
“…The observed LPS-induced decline in CD18 MFI was unexpected, but the interesting findings by Wong et al allow us to raise the hypothesis that our findings reflect an adequate immune response to acute LPS-induced inflammation with a profitable downregulation of CD18 and a subsequent attenuated inflammatory response. Findings similar to ours have been described in vivo on neutrophils in LPS-challenged rodents [20], in which sham treatment (saline, anaesthesia) per se decreased MFI CD11a ⁄ CD18 at 6 h, and LPS contributed with a further decline at 1 and 6 h. CD18 was downregulated by LPS in monocytes in a murine study [28]. In contrast, Rezaie-Majd et al [18] found upregulation of CD18 in stimulated PBMC, and the discrepancy between their and our results could be explained by the use of TNF-a, and not LPS, as stimulus.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The observed LPS-induced decline in CD18 MFI was unexpected, but the interesting findings by Wong et al allow us to raise the hypothesis that our findings reflect an adequate immune response to acute LPS-induced inflammation with a profitable downregulation of CD18 and a subsequent attenuated inflammatory response. Findings similar to ours have been described in vivo on neutrophils in LPS-challenged rodents [20], in which sham treatment (saline, anaesthesia) per se decreased MFI CD11a ⁄ CD18 at 6 h, and LPS contributed with a further decline at 1 and 6 h. CD18 was downregulated by LPS in monocytes in a murine study [28]. In contrast, Rezaie-Majd et al [18] found upregulation of CD18 in stimulated PBMC, and the discrepancy between their and our results could be explained by the use of TNF-a, and not LPS, as stimulus.…”
Section: Discussionsupporting
confidence: 88%
“…allow us to raise the hypothesis that our findings reflect an adequate immune response to acute LPS‐induced inflammation with a profitable downregulation of CD18 and a subsequent attenuated inflammatory response. Findings similar to ours have been described in vivo on neutrophils in LPS‐challenged rodents [20], in which sham treatment (saline, anaesthesia) per se decreased MFI CD11a/CD18 at 6 h, and LPS contributed with a further decline at 1 and 6 h. CD18 was downregulated by LPS in monocytes in a murine study [28]. In contrast, Rezaie‐Majd et al.…”
Section: Discussionsupporting
confidence: 85%
“…Pretreatment of macrophages with RD-LPS induces tolerance of the cells towards NO induction by toxic LPS. Second, like LPS, RD-LPS induces CD11b and CD18 integrin expression on PMN [37]. Furthermore, RD-LPS reduces lethality in mice after induction of bacterial peritonitis [37].…”
Section: Induction Of Tlr-4 Expressionmentioning
confidence: 95%
“…Furthermore, RD-LPS reduces lethality in mice after induction of bacterial peritonitis [37]. And third, RD-LPS increases the production of white blood cells in healthy animals [37], which might be an extra benefit because immediately after infection, a systemic leukopenia is established [93].…”
Section: Induction Of Tlr-4 Expressionmentioning
confidence: 99%
“…Thus, we suggest that gamma-ray irradiation modified that part of the LPS molecule complex, possibly in the lipid A moiety [22], which is known to be responsible for toxicity including the enhanced production of above cytokines. However, other parts of the irradiated molecule could activate their specific binding sites, leading to the observed effects of RD-LPS [17,[25][26][27].…”
Section: Discussionmentioning
confidence: 99%